The Effectiveness of Bean Juice in Hemoglobin levels in Pregnant to Preventing Anemia - Apryanti, Yohana Putri; Br Sembiring, Desi (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2025)
ABSTRACTOne of the changes that occur due to the process of pregnancy in pregnant women is hematological changes such as a decrease in hemoglobin levels in pregnant women caused by the process of hemodilution with a volume of 30-40% during pregnancy and ending at week 32-44 of gestational age So that it requires special attention in fulfilling nutritional intake, because if it is not fulfilled it will be able to cause a decrease in hemoglobin levels and cause anemia The purpose of the study was to determine whether there was an effect of giving bean juice to prevent anemia in pregnant women. This research method is Pre-experiment with Quasi experimental design method, namely two group pretest - postest. The sampling technique is a purposive sample of 22 people with the inclusion criteria set, the intervention given in accordance with the SOP and the Hb level is measu with an easy touch tool. Data analysis consisted of bivariate with pai sample t-test. And the results of the study with a Pvalue of 0.000 < (0.05), it was concluded that there was a difference in the increase in haemoglobin levels in the experimental group. And there is a significant difference in bean juice on the increase in haemoglobin levels with a Sig value. (2-tailed) of 0.000 is smaller than alpha 0.05 (p<α 0.05).